Introduction of Feed Processing Technology for Goats in the Batang Sinama Farmer Group - Engki Zelpina; Yurni Sari Amir; Delli Lefiana; Prima Silvia Noor; Sujatmiko; Ramond Siregar; Ulva Mohtar Lutfi; Rezki Dedi; Hamidah (Jurnal Pengabdian Masyarakat Bestari, 2023)
This was marked by obtaining goat livestock assistance for the group and the existence of joint land processing activities carried out by the group. One of the group's potentials in raising goats is the existence of corn plants that are managed by the group. In terms of feeding goats, the group still relies on providing forage in the form of field grass or corn straw obtained during harvest. The problem found in raising goats is that there is potential that has not been utilized by the group, namely the use of corn straw as animal feed which is continuously available and the low performance of the goats. The service activities carried out include counseling about feed processing to fulfill goat nutrition, goat health checks, practice of fermenting corn straw, making feed supplements and administering worm medicine. The method of implementing service is through lectures, discussions and direct practice. The results of the service that has been carried out are that the group knows the process of making fermented corn straw and feed supplements, adds to the group's insight into livestock care and knows about cases of worms in goats which can reduce goat performanThis was marked by obtaining goat livestock assistance for the group and the existence of joint land processing activities carried out by the group. One of the group's potentials in raising goats is the existence of corn plants that are managed by the group. In terms of feeding goats, the group still relies on providing forage in the form of field grass or corn straw obtained during harvest. The problem found in raising goats is that there is potential that has not been utilized by the group, namely the use of corn straw as animal feed which is continuously available and the low performance of the goats. The service activities carried out include counseling about feed processing to fulfill goat nutrition, goat health checks, practice of fermenting corn straw, making feed supplements and administering worm medicine. The method of implementing service is through lectures, discussions and direct practice. The results of the service that has been carried out are that the group knows the process of making fermented corn straw and feed supplements, adds to the group's insight into livestock care and knows about cases of worms in goats which can reduce goat performan